Macro-engineering seawater in unique environments arid lowlands and water bodies rehabilitation - Badescu, Viorel; Cathcart, Richard B. (Environmental science and engineering., 2011)
The subjects refer to histories of ancient and modern use of seacoasts; possible macro-projects capable of massive changes in the coastlines of the Dead Sea, Red Sea and Persian Gulf caused by canal and massively scaled hydropower dam installations; relevant macro-projects for the Black Sea and Baltic Sea; possibilities of refreshment of the Aral Sea and Iran's Lake Uremia with seawater or river freshwater importation macro-projects; potential rehabilitation of some vital arid zone regions now dominated by moving or movable surface granular materials using unique and unusual macro-projects; seawater flooding of land regions situated below present-day global sea-level; harnessing energy and obtaining freshwater from the world's salt-laden ocean by modern industrial means; various macro-projects designed specifically for the protection (reduction of vulnerability) of particular Earth geographical regions.